2020
DOI: 10.1111/fcp.12554
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine inhibits angiogenesis through oxidative stress‐dependent inhibition of Akt/mTOR and activation of AMPK

Abstract: Although substantial evidence shows the link of local anesthesia and decreased tumor recurrence, the role of amide‐linked local anesthetics, particularly bupivacaine, on angiogenesis (a hallmark of tumor progression and metastasis) has not been revealed. In this work, we demonstrate the anti‐angiogenic activity of bupivacaine and its underlying mechanism in endothelial cells. We show that bupivacaine inhibits early stage of capillary network formation via suppressing endothelial cell migration without affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…In agreement with our findings, the LINC00470 expression was noticeably enhanced in gastric cancer tissues and cell lines, which was likewise associated with poor prognosis, distant metastasis, and tumor-node-metastasis stage (8). Additionally, LINC00470 plays a vital role in the tumorigenesis of glioblastoma and its high expression correlates with poor prognosis of patients with glioblastoma (18). Furthermore, LINC00470 can promote malignant behaviors of hepatocellular carcinoma cells (26), supporting the oncogenic effect of LINC00470 in cancers.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our findings, the LINC00470 expression was noticeably enhanced in gastric cancer tissues and cell lines, which was likewise associated with poor prognosis, distant metastasis, and tumor-node-metastasis stage (8). Additionally, LINC00470 plays a vital role in the tumorigenesis of glioblastoma and its high expression correlates with poor prognosis of patients with glioblastoma (18). Furthermore, LINC00470 can promote malignant behaviors of hepatocellular carcinoma cells (26), supporting the oncogenic effect of LINC00470 in cancers.…”
Section: Discussionsupporting
confidence: 90%
“…[12] In endothelial cells, bupivacaine suppresses angiogenesis through oxidative stress-dependent inhibition of the Akt/mTOR pathway and activation of the AMPK pathway. [46] In our study, we found that bupivacaine reduced the protein levels of total and phosphorylated EGFR and ERBB3, thus impaired the activation of downstream PI3K/Akt and MAPK pathways in HCC cells. It is reported that local anesthetic Lidocaine inhibits the shedding of heparin-binding epidermal growth factor-like growth factor (HB-EGF), thus reduced EGFR phosphorylation and suppressed the invasion of human cancer cells.…”
Section: Discussionsupporting
confidence: 49%
“…Zhai et al ( 53 ) have proved that overexpressed SIRT1 increases the phosphorylation levels of PI3K and AKT, thereby inhibiting the apoptosis of cardiomyocytes induced by high glucose and reducing its oxidative stress response. MTOR is an important downstream target of AKT and takes part in the expression and transcription of related proteins and genes, thus affecting biological activities such as inflammation, oxidative stress, apoptosis, and so on ( 54 , 55 ). The over-expressed SIRT1 activates PI3K through tyrosine kinase receptor, then the activated PI3K promotes the phosphorylation of AKT, activates MTOR, and inhibits oxidative stress and inflammation ( 56 ).…”
Section: Resultsmentioning
confidence: 99%